PENGETAHUAN IBU TENTANG MANFAAT GERAKAN PIJAT PADA BAYI - Hafsanah Nikmahtullah; Joni Siagian (Jurnal Keperawatan Dan Kesehatan Holistik, 2026)
Baby massage is a tactile stimulation. Baby massage is a form of communication that does not involve the mother and baby. Baby development usually occurs in children aged 0–6 months. The purpose of this study was to analyze mothers' knowledge about the value of massage movements on babies in Neighborhood IV, Karang Anyer Village, Kisaran Timur District, Asahan Regency. This study used a Descriptive Survey method developed based on research. For example, currently there are 33 people born in Village IV Karang Anyer, Kisaran Timur District, Asahan Regency. The results of the mother's research on the overall baby massage movement were 7.56 or 76%, indicating that the mother's knowledge was in the "Good" category. This was done to increase awareness of the benefits of massage movements on babies and analyze information obtained from social media and the results of relevant and enlightening health-related activities.